Size control: the developmental physiology of body and organ size regulation. (25th March 2015) - Gokhale, Rewatee H.; Shingleton, Alexander W.
<x xml:space="preserve">Abstract</x> The developmental regulation of final body and organ size is fundamental to generating a functional and correctly proportioned adult. Research over the last two decades has identified a long list of genes and signaling pathways that, when perturbed, influence final body size. However, body and organ size are ultimately a characteristic of the whole organism, and how these myriad genes and pathways function within a physiological context to control size remains largely unknown. In this review, we first describe the major size‐regulatory signaling pathways: the Insulin/IGF‐, RAS/RAF/MAPK‐, TOR‐, Hippo‐, and JNK‐signaling pathways. We then explore what is known of how these pathways regulate five major aspects of size regulation: growth rate, growth duration, target size, negative growth and growth coordination. While this review is by no means exhaustive, our goal is to provide a conceptual framework for integrating the mechanisms of size control at a molecular‐genetic level with the mechanisms of size control at a physiological level. WIREs Dev Biol 2015, 4:335–356. doi: 10.1002/wdev.181 For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article.